Menjelajahi Tren Design Thinking dalam Pendidikan: Tinjauan Literatur Sistematis dari Jurnal Terindeks Web of Science dalam Desain Instruksional dan Desain Sistem Instruksional - Lardiatama, Trada; Wigati, Wigati (LP. Ma'arif Janggan Magetan, 2023)
The use of Design Thinking in the field of education has become a major highlight as a relevant problem solving method. Problem solving ability is one of the essential competencies in the context of 21st century education. This research uses content analysis of a number of articles contained in the Web of Science (WOS) database, with the main focus on the application of Design Thinking (DT) within the framework of Instructional Design (ID) and/or Instructional System Design (ISD). This research aims to complement the previous report,